Paleoclimate changes and ecosystem responses of the Bulgarian Black Sea zone during the last 26000 years - Filipova-Marinova, Mariana; Pavlov, Danail; Slavova, Krasimira (Nature Conservation, 2024)
Multi-proxy analysis (spore-pollen, dinoflagellate cysts, other non-pollen palynomorphs (NPPs), radiocarbon dating and lithology) was performed on marine sediments from three new cores retrieved during the two cruise expeditions on board the Research Vessel “Akademik” in 2009 and 2011. The Varna transect comprises three cores extending from the outer shelf, continental slope and deep-water zone. The record spans the last 26000 years (all ages obtained in this study are given in calendar years BP (cal. yrs BP)). The pollen record reveals the spreading of steppe vegetation dominated by Artemisia and Chenopodiaceae, suggesting cold and dry environments during the Late Pleniglacial – Oldest Dryas (25903–15612 cal. yrs BP). Stands of Pinus and Quercus reflect warming/humidity increase during the melting pulses (19.2–14.5 cal. ka BP) and the Late Glacial interstadials Bølling and Allerød. The Younger Dryas (13257–11788 cal. yrs BP) coldest and driest environments are clearly demonstrated by the maximum relative abundance of Artemisia and Chenopodiaceae. During the Early Holocene (Preboreal and Boreal chronozones, 11788–8004 cal. yrs BP), Quercus appeared as a pioneer species and, along with other temperate deciduous arboreal taxa, formed open deciduous forests as a response to the increased temperature. The rapid expansion of these taxa indicates that they survived in Glacial refugia in the coastal mountains. During the Atlantic chronozone (8004–5483 cal. yrs BP), optimal climate conditions (high humidity and increased mean annual temperatures) stimulated the establishment of species-rich mixed temperate deciduous forests. During the Subboreal chronozone (5483–2837 cal. yrs BP), Carpinus betulus and Fagus expanded simultaneously and became more important components of mixed oak forests and probably also formed separate communities. During the Subatlantic chronozone (2837 cal. yrs BP to pre-industrial time), climate-driven changes (an increase of humidity and a cooling of the climate) appear to be the main drivers of the specific vegetation succession expressed by increased abundance of Alnus, Fraxinus excelsior and Salix along with lianas, suggesting formation of flooded riparian forests (so called ‘Longoz’) lining the river valleys along the Black Sea coast. The first indicators of farming and other human activities have been recorded since 7074 cal. yrs BP. The dinoflagellate cyst (dinocyst) assemblages have been analysed to assess the changes in the Black Sea environment over the last 26000 years in terms of fluctuation in paleoproduction and surface water conditions related to changes in climate, freshwater input and Mediterranean water intrusion. Two major dinocyst assemblages were distinguished: one dominated by stenohaline freshwater/brackish-water species and a successive one dominated by euryhaline marine species. The changes in the composition of the assemblages occurred at 7668 cal. yrs BP. The abrupt decrease of stenohaline freshwater/brackish-water species Pyxidinopsis psilata and Spiniferites cruciformis was followed upwards by a gradual increase in euryhaline marine species, such as Lingulodinium machaerophorum, Spiniferites belerius, S. bentorii and acritarch Cymatiosphaera globulosa. The first occurrence of euryhaline marine species took place synchronously with the onset of sapropel deposition. Modern marine conditions were established after 6417 cal yrs BP when an abundance of Mediterranean-related species, such as Operculodinium centrocarpum and Spiniferites mirabilis, along with other heterotrophic species, occurred. After the stable cold and dry environment during the Last Glacial Maximum, the phytoplankton record of core AKAD 11-17 shows that Pediastrum boryanum var. boryanum has a cyclical abundance associated with the deposition of four red-brown clay layers between 19.2 and 14.5 cal. ka BP. This event is associated with the major melting phase of European Ice drained by the Danube and Dnieper Rivers in response to climate warming observed after the end of the Last Glacial Maximum. During the Early Holocene, P. psilata, characterised by a preference to warmer temperatures, demonstrates its ecological optimum for growth concerning SST reaching maximum relative abundance of 94% between 11072 and 8638 cal. yrs BP. This maximum was interrupted by an abrupt significant short-term decrease in the relative abundance of P. psilata centred between 8500 and 8300 cal. yrs BP reflecting cold conditions similar to those of Younger Dryas. This finding, also confirmed by the rapid significant decrease of arboreal pollen, particularly of Quercus in the same studied core, is considered a regional expression of the well-known ‘8.2 ka cold event’ which is commonly linked to a meltwater-related perturbation of the Atlantic Meridional Overturning Circulation (AMOC) and associated collapse of oceanic northward heat transport. Our fossil pollen and dinocyst data confirm that the high amplitude temperature anomaly associated with ‘the 8.2 ka cold event’ may have also occurred in south-eastern Europe, at lower latitudes of the western Black Sea coastal area, most probably due to atmospheric transition and/or river discharge.
Publisher: Pensoft Publishers